Viewing the use of open educational resources through a community of practice lens: a case study of teachers' use of the Everything Maths and Everything Science open textbooks - Cartmill, Erna Theresa (University of Cape Town, 2015)
This study answers to th e quest ions of why and how the "Everything Maths" and "Everything Science" open textbooks are used, and to what extent a Community of Practice (Wenger, 2006) has formed around the use of these open textbooks, are informed by a case study, comprising of interviews with nine South African high-school teachers using these open educational resources. The Community of Practice theory provided a useful lens through which to code, analyse and view utterances made. Findings indicate that while financial reasons for using the open textbooks are important, pedagogical reasons, of quality and scope of content, are more valued by teachers. Also important are the availability of the open textbooks in a variety of formats, the potential for teachers to develop social learning (Brown, 2008) skills, learners to study independently, the interactive features, and online availability of the open textbooks. A Community of Practice, while not formalised, exists around the use of these open textbooks and can be classified as an Active Community (Kim, Hong and Suh 2012).